Snapshots of a Changing Scholarly Communications Environment - Prosser, David C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Almost two years after the formation of SPARC Europe, the LIBER pre-conference seminar in St Petersburg gave an excellent opportunity to review progress on the road to achieving the aims of SPARC Europe. The traditional models of scholarly communication are increasingly being shown to be antiquated and insufficiently flexible to adapt to the new environment. SPARC Europe calls for far reaching changes in the way we approach scholarly communications. The talks in the seminar provide snapshots of the changing environment. They highlight the activities being taken at all levels by a wide variety of stakeholders in the scholarly communications process: Small and society publishers are developing alternatives to inflexible and restrictive 'Big Deals'; funding bodies and research organisations worldwide are becoming aware of issues surrounding scholarly communication; institutional repositories are providing new communications channels; and libraries are investigating new directions and taking on new roles. This paper will expand on some of these recent developments.